Mitochondrial Calcium Increase Induced by RyR1 and IP3R Channel Activation After Membrane Depolarization Regulates Skeletal Muscle Metabolism - Díaz-Vegas, Alexis R.; Cordova, Alex; Valladares, Denisse; Llanos, Paola; Hidalgo, Cecilia; Gherardi, Gaia; De Stefani, Diego; Mammucari, Cristina; Rizzuto, Rosario; Contreras-Ferrat, Ariel; Jaimovich, Enrique (Frontiers in Physiology, 2018)
Aim: We hypothesize that both type-1 ryanodine receptor (RyR1) and IP3-receptor (IP3R) calcium channels are necessary for the mitochondrial Ca2+ increase caused by membrane depolarization induced by potassium (or by electrical stimulation) of single skeletal muscle fibers; this calcium increase would couple muscle fiber excitation to an increase in metabolic output from mitochondria (excitation-metabolism coupling). Methods: Mitochondria matrix and cytoplasmic Ca2+ levels were evaluated in fibers isolated from flexor digitorium brevis muscle using plasmids for the expression of a mitochondrial Ca2+ sensor (CEPIA3mt) or a cytoplasmic Ca2+ sensor (RCaMP). The role of intracellular Ca2+ channels was evaluated using both specific pharmacological inhibitors (xestospongin B for IP3R and Dantrolene for RyR1) and a genetic approach (shIP3R1-RFP). O2 consumption was detected using Seahorse Extracellular Flux Analyzer. Results: In isolated muscle fibers cell membrane depolarization increased both cytoplasmic and mitochondrial Ca2+ levels. Mitochondrial Ca2+ uptake required functional inositol IP3R and RyR1 channels. Inhibition of either channel decreased basal O2 consumption rate but only RyR1 inhibition decreased ATP-linked O2 consumption. Cell membrane depolarization-induced Ca2+ signals in sub-sarcolemmal mitochondria were accompanied by a reduction in mitochondrial membrane potential; Ca2+ signals propagated towards intermyofibrillar mitochondria, which displayed increased membrane potential. These results are compatible with slow, Ca2+-dependent propagation of mitochondrial membrane potential from the surface towards the center of the fiber. Conclusion: Ca2+-dependent changes in mitochondrial membrane potential have different kinetics in the surface versus the center of the fiber; these differences are likely to play a critical role in the control of mitochondrial metabolism, both at rest and after membrane depolarization as part of an “excitation-metabolism” coupling process in skeletal muscle fibers.